Social knowledge [ using social media to know what you know - Girard, JoAnn L.; Girard, John P. , 1961- (Gale virtual reference library, 2011)
"This book provides relevant theoretical frameworks, latest empirical research findings, and practitioners' best practices social knowledge, for improving understanding of the strategic role of social knowledge in business, government, or non-profit sectors" -- Provided by publisher